2022
DOI: 10.3389/fimmu.2022.893179
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of PD-1/PD-L1 Inhibitors in Cancer Patients With Preexisting Autoantibodies

Abstract: BackgroundProgrammed cell death protein-1/programmed cell death ligand-1 (PD-1/PD-L1) inhibitors therapy is now a routine scheme in cancers. However, the effect of preexisting autoantibodies on the safety and efficacy of PD-1/PD-L1 inhibitors in cancer patients is not well understood.MethodsThe present retrospective cohort study evaluated the safety and efficacy of PD-1/PD-L1 inhibitors in patients with preexisting autoantibodies. Patients who received PD-1/PD-L1 inhibitors in the Department of Medical Oncolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Similarly, although De Moel et al ( 106) also recorded an increase in rheumatologic AAbs from baseline in late-stage melanoma patients (who were antibody negative pre-treatment), no association with any irAEs was observed. Several reports have also found no significant association between pre-existing ANAs in various cancer patients prior to ICI therapy, with the occurrence of irAEs (97,99,103,104). Despite the temporal resemblance of classic autoimmune diseases with irAEs, it appears that their mechanisms might be different and whether an increase or decrease in classic rheumatological AAbs is beneficial for the prediction of irAEs remains controversial and requires further investigation.…”
Section: Autoantibodies As Biomarkers Of Immune Related Adverse Eventsmentioning
confidence: 98%
“…Similarly, although De Moel et al ( 106) also recorded an increase in rheumatologic AAbs from baseline in late-stage melanoma patients (who were antibody negative pre-treatment), no association with any irAEs was observed. Several reports have also found no significant association between pre-existing ANAs in various cancer patients prior to ICI therapy, with the occurrence of irAEs (97,99,103,104). Despite the temporal resemblance of classic autoimmune diseases with irAEs, it appears that their mechanisms might be different and whether an increase or decrease in classic rheumatological AAbs is beneficial for the prediction of irAEs remains controversial and requires further investigation.…”
Section: Autoantibodies As Biomarkers Of Immune Related Adverse Eventsmentioning
confidence: 98%
“…However, the results were somewhat inconsistent when investigating which specific autoantibody was the main contributor to the association with irAEs. The most promising and well-studied autoantibody was anti-nuclear antibody [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], followed by rheumatoid factor [ 13 , 22 ], both studied in multiple types of solid tumors, including malignant melanoma and NSCLC. Some studies suggested a positive association between pre-existing autoantibodies and the development of any irAE [ 14 , 16 , 17 , 18 , 19 ], but some reported no association [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…The most promising and well-studied autoantibody was anti-nuclear antibody [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], followed by rheumatoid factor [ 13 , 22 ], both studied in multiple types of solid tumors, including malignant melanoma and NSCLC. Some studies suggested a positive association between pre-existing autoantibodies and the development of any irAE [ 14 , 16 , 17 , 18 , 19 ], but some reported no association [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In summary, the evidence is conflicting, and they do not seem to be a reliable predictor for irAE in general when used alone.…”
Section: Biomarkersmentioning
confidence: 99%
“…Recent evidence has focused on the sensitivity of autoantibodies to identify patient risk of developing irAEs when treated with cancer immunotherapy and mainly, immune checkpoint inhibitors [28,29]. Our group has previously utilised and validated a customized auto-antibody panel with the ability to detect a wide range of both IgM and IgG antibodies against 161 self-antigens [30,31].…”
Section: Autoantibodiesmentioning
confidence: 99%